2014
DOI: 10.1016/j.bmc.2014.04.066
|View full text |Cite
|
Sign up to set email alerts
|

Novel synthetic route for antimalarial benzo[a]phenoxazine derivative SSJ-183 and two active metabolites

Abstract: A productive synthesis of benzo[a]phenoxazine derivative SSJ-183 (1), a promising lead for antimalarial agents, was developed using a one pot procedure. Furthermore, N-deethylated metabolite 3 and bis-N,N-deethylated metabolite 4 were synthesized by the application of the method. The metabolites 3 and 4 showed comparable and ∼2-fold increased activities against drug-sensitive and drug-resistant Plasmodium falciparum parasites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…1) by submitting these to contemporary preclinical screening protocols and assessment of pharmacokinetic (PK) profiles. Phenoxazines have notable biological activities, and several are potently active against malaria (11,28,29). To our knowledge, however, no reports have described evaluation of the in vitro efficacies of the representative phenoxazine compounds against M. tuberculosis coupled with quantification of absorption, distribution, metabolism, and excretion (ADME) parameters and in vivo drug concentrations.…”
mentioning
confidence: 99%
“…1) by submitting these to contemporary preclinical screening protocols and assessment of pharmacokinetic (PK) profiles. Phenoxazines have notable biological activities, and several are potently active against malaria (11,28,29). To our knowledge, however, no reports have described evaluation of the in vitro efficacies of the representative phenoxazine compounds against M. tuberculosis coupled with quantification of absorption, distribution, metabolism, and excretion (ADME) parameters and in vivo drug concentrations.…”
mentioning
confidence: 99%
“…In another report, one-pot synthesis of benzo[a]phenoxazine derivative SJ-183 lead 14 a and its N-de-ethylated 14 b and bis-N,N-deethylated 14 c metabolites were described. [29] Their antimalarial activities showed comparable and approximately two-fold increased IC 50 against drug-sensitive and drugresistant Plasmodium falciparum parasites ( Table 2). Previously, higher activities against P. falciparum were recorded in the in-vitro screening of benzo[a]phenoxazine class of SJ-183 compounds possessing hetero-aromatic rings on position-6 and compound 14 a, in particular, showed the rapid onset of action comparable to artesunate antimalarial drug.…”
Section: Phenoxazines As Antimalarial Agentsmentioning
confidence: 98%
“…During our continuing project for developing new generation of PSs [ 7 , 8 , 9 , 10 ], the benzo[ a ]phenoxazinium chlorides dyes came to our attention due to their good photostability, high molar absorption, long-wavelength absorption, and relative low fluorescence quantum yield [ 11 , 12 , 13 ]. Literature survey indicated that benzo[ a ]phenoxazinium derivatives exhibited antifungal [ 12 , 14 ], and antimalarial activity [ 15 ], and especially functioned as PSs in antimicrobial PDT [ 15 , 16 , 17 , 18 ]. However, to our knowledge, the potential anticancer PDT of benzo[ a ]phenoxazinium dyes has been little investigated [ 19 ].…”
Section: Introductionmentioning
confidence: 99%